2012 IEEE International Conference on Robotics and Automation 2012
DOI: 10.1109/icra.2012.6225110
|View full text |Cite
|
Sign up to set email alerts
|

Online calibration of vehicle powertrain and pose estimation parameters using integrated dynamics

Abstract: Abstract-This paper presents an online approach to calibrating vehicle model parameters that uses the integrated dynamics of the system. Specifically, we describe the identification of the time constant and delay in a first-order model of the vehicle powertrain, as well as parameters required for pose estimation (including position offsets for the inertial measurement unit, steer angle sensor parameters, and wheel radius). Our approach does not require differentiation of state measurements like classical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This paper unifies and elaborates on previous publications by the authors: Kelly (2004a) applied IPEM to 2D odometry calibration, Rogers-Marcovitz and applied IPEM to slip model calibration, Seegmiller et al (2011) demonstrated slip model calibration in 3D on Crusher and introduced stochastic calibration, and later applied IPEM to powertrain model and sensor calibration (Seegmiller et al, 2012). Note that the name "IPEM" was not used in previous papers, but was chosen for this journal paper.…”
Section: Related Workmentioning
confidence: 73%
See 2 more Smart Citations
“…This paper unifies and elaborates on previous publications by the authors: Kelly (2004a) applied IPEM to 2D odometry calibration, Rogers-Marcovitz and applied IPEM to slip model calibration, Seegmiller et al (2011) demonstrated slip model calibration in 3D on Crusher and introduced stochastic calibration, and later applied IPEM to powertrain model and sensor calibration (Seegmiller et al, 2012). Note that the name "IPEM" was not used in previous papers, but was chosen for this journal paper.…”
Section: Related Workmentioning
confidence: 73%
“…When velocity commands change, the response of many powertrains can be modeled adequately by a time delay and a first-order transient response. In Seegmiller et al (2012), the authors present how the IPEM formulation can be used to identify the time delay and time constant. A brief summary is presented here, but please refer to the original paper for a full discussion of results and related work.…”
Section: Application: Identifying Powertrain Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the slip-compensated vehicle model, we can achieve improved dead-reckoning relative to naive integration of the odometry measurements (3). By assumption, the perturbative (i.e.…”
Section: Odometry Measurementmentioning
confidence: 99%
“…We use Integrated Perturbative Dynamics (IPD) to learn the mapping between control inputs and resultant vehicle motion by calibrating the vehicle's mobility model online using an extended Kalman filter. Past work has used IPD to identify systematic and stochastic models of wheel slip [2], powertrain dynamics, and odometry parameters [3].…”
Section: Introductionmentioning
confidence: 99%